Crisis management, destination recovery and sustainability tourism at a crossroads - Hassan, Azizul; Kennell, James; Mohanty, Priyakrushna; Sharma, Anukrati 1981- (Routledge, 2023)
"The COVID-19 pandemic brought travel to a halt and the global tourism industry has been one of the sectors hit hardest during the pandemic. This book looks at how the tourism industry could enhance its resilience and prepare for future crises more effectively. The book provides insights into the economic, social, geopolitical and environmental implications of the COVID-19 pandemic on the tourism and hospitality industries and the responses in diverse, international contexts. It highlights key concepts and includes cases with real life applications. The book also discusses future research directions in a post-pandemic scenario. This book will be an invaluable resource for practitioners in the areas of tourism and crisis management and for readers to compare and contrast tourism destination recovery and crisis management practices through different research methodologies and settings"--